(3GdQMdI GdedcjI hGdZGOI GdMdjI dML SfI (B1305(3g`s - (3MSf eUHM GdMdi GdTjHGfis; (3MSf eUHM GdMdj GdTjHGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi aQV GdML Ydi ef GSJWGY Edjg SHjdkG aJCgHfG ddeSjQ Edi Pdc hfMf ai ZGjI GdCfS hGdWQH s
(3BNQgG (B:s
(3hdc GdeRGjG GdZQai JYOGOgG CYjJ dSGf GdTcQ ai (B( (3MUGgG (B) (3hgPG BNQ eG CQOfG EKHGJg ai gPg GdQMdI GdecjI hGdZGOI GdMdjI hGddg MSHi JeJ s
(3HgG fXGe GdJYbjHIs
(3HChQGbgG GdChdi hGdCNjQI JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B119 s
Keywords: (3GdJGQjNs